Hukum ekonomi Syariah Transformasi Akad Wadî’ah pada Tabungan Emas Bank Syariah Indonesia - Agus Salim (Universitas Muhammadiyah Surabaya, 2023)
Abstrak This research discusses the transformation of wadî'ah contracts in Indonesian Sharia Bank gold savings. The wadî'ah contract is basically a tabarru' contract or a virtue contract. In its implementation, the wadî'ah contract is a contract to entrust the safekeeping of goods to a person who is trusted to look after and maintain them without compensation, and can be taken or returned at any time. The implementation of the wadî'ah contract like this turns out to be different from the implementation of the wadî'ah contract on the gold savings of Bank Syariah Indonesia (BSI). Where in its implementation many provisions have changed from the form of the wadî'ah contract in classical jurisprudence. This research article will show the transformation of the wadî'ah contract from classical fiqh to the wadî'ah contract which is implemented in BSI gold savings. Temporary findings are that the BSI gold savings wadî'ah agreement applies provisions for a deposit fee to be paid annually, a physical collection fee for the gold and a maintenance fee for the goods entrusted or a delay fee due to delays in physical gold collection. Keyword: Akad Wadî’ah, Contract Transformation, Gold Savings, Bank Syariah Indonesia